Mental health conditions of Chinese international students and associated predictors amidst the pandemic - Linke Yu; Ying Cao; Yiran Wang; Tianxing Liu; Alison MacDonald; Fiona Bian; Xuemei Li; Xiaorong Wang; Zheng Zhang; Peizhong Peter Wang; Lixia Yang (Elsevier, 2023)
The current study aims to examine the mental health conditions and the associated predictors among Chinese international students. A sample of 256 Chinese international students aged 16 or above living primarily in Canada were asked to complete an online survey. Mental health conditions were assessed with the Depression, Anxiety, and Stress Scale-21 and the Physical and Mental Health Summary Scales. 15.3%, 20.4%, and 10.5% of respondents reported severe to extremely severe depression, anxiety, and stress levels, respectively. Univariate analysis of variance models and multiple linear regression models identified education and financial status as significant sociodemographic predictors while controlling for the effect of physical health status. Higher financial status and lower level of education were associated with better mental health conditions. These findings shed light on our understanding of mental health conditions and the risk factors among Chinese international students during the COVID-19 pandemic.